Generalised water flow rate control strategy for optimal part load operation of ground source heat pump systems. (15th July 2015) - Edwards, K.C.; Finn, D.P.
Highlights: Control strategy developed for predicting optimal GSHP water flow rate. Strategy operates under part load conditions to improve seasonal performance. Control strategy requires minimal on-line inputs and design data. Evaluation of strategy against nominal flow using GSHP simulation models. Potential improvement in seasonal performance of between 20% and 40% observed. Abstract: A control strategy was developed to predict optimal ground source heat pump water flow rates under part load operation. Using this strategy, optimal flow rates are calculated from available design data and minimal on-line measurements. The optimal control strategy was evaluated with validated single speed and tandem speed ground source heat pump simulation models in both heating and cooling mode. A range of building load profiles were implemented when analysing heat pump system performance. The optimal strategy was shown to result in an improvement in system performance when compared to nominal flow rate operation, particularly for low load conditions. Due to the prevalence of low load operation over a heating or cooling season, the seasonal system performance (SPF3 ) was shown to increase by between 20% and 40% when using the optimal strategy.